2017
DOI: 10.1021/acssynbio.6b00374
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRi–sRNA: Transcriptional–Translational Regulation of Extracellular Electron Transfer in Shewanella oneidensis

Abstract: Extracellular electron transfer (EET) in Shewanella oneidensis MR-1, which is one of the most well-studied exoelectrogens, underlies many microbial electrocatalysis processes, including microbial fuel cells, microbial electrolysis cells, and microbial electrosynthesis. However, regulating the efficiency of EET remains challenging due to the lack of efficient genome regulation tools that regulate gene expression levels in S. oneidensis. Here, we systematically established a transcriptional regulation technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 63 publications
1
65
0
Order By: Relevance
“…As expected, only slight downregulation of actII4 (≈70% of the control) was observed in the strain with pSET‐dCas9‐ actII4‐ Out‐S0 (targeting outside of the gene) at 48 h, but the repression extent was much lower than the strains with sgRNAs targeting the coding region. The results presented above clearly demonstrated that our CRISPRi system could be used for efficient gene repression in S. coelicolor , and further confirmed that sgRNAs targeting the coding regions of target genes on the NT strand are very effective for gene repression as reported in other bacteria …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, only slight downregulation of actII4 (≈70% of the control) was observed in the strain with pSET‐dCas9‐ actII4‐ Out‐S0 (targeting outside of the gene) at 48 h, but the repression extent was much lower than the strains with sgRNAs targeting the coding region. The results presented above clearly demonstrated that our CRISPRi system could be used for efficient gene repression in S. coelicolor , and further confirmed that sgRNAs targeting the coding regions of target genes on the NT strand are very effective for gene repression as reported in other bacteria …”
Section: Resultssupporting
confidence: 81%
“…Many studies showed that sgRNAs targeting the promoter regions are very effective for gene repression irrespective of whether they are targeted to the template (T) or nontemplate strand (NT); however, when sgRNAs are targeted to the coding region, effective repressive effects are only observed on the NT strand . Considering that the promoter regions of most genes in Streptomyces are unknown, in this study, all sgRNAs were designed to target the NT strand of gene coding regions, which were conducted by the software CRISPRy to minimize off‐target effects .…”
Section: Resultsmentioning
confidence: 99%
“…We found that Cas9 must be tightly regulated since high Cas9 expression leads to a loss in cell viability, as shown in other bacteria (Cobb et al 2014;Cui et al 2018;Huang et al 2015;Wang et al 2018). CRISPRi was also recently applied in S. oneidensis for transient control of gene expression with the defective dCas9 protein (Cao et al 2017), however, CRISPRi is not a tool for site-directed mutagenesis (Table 4.2). (Saltikov & Newman 2003;Blomfietd et al 1991;Corts et al 2019), b CFU/µg DNA in E. coli MG1655 (Gray et al 2015;Yang et al 2014), c Measured as repression of GFP expression (Peters et al 2016;Cao et al 2017), d Determined as the number of recombinants among the total surviving cells (this work).…”
Section: )mentioning
confidence: 64%
“…Then, we examined the transcriptional repression capability of CRISPRi on gene expression by co-expressing a specific sgRNA. sgRNA- gfp was designed to target on the non-template strand of GFP at a position ∼38 nucleotides downstream of the start codon to expect a high repression efficiency 25 . The plasmid Sg-Hgfp ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%